2013
DOI: 10.1103/physrevd.88.025031
|View full text |Cite
|
Sign up to set email alerts
|

Bound on noncommutative standard model with hybrid gauge transformation via lepton flavor conservingZdecay

Abstract: The Z → e + e − decay is studied basing on the noncommutative standard model (NCSM) with the hybrid gauge transformation. It is shown that if the latter is not included, the noncommutative correction to the amplitude of the Z → e + e − appears only as a phase factor, so that there is no new physical effect on the decay width. However, when the hybrid gauge transformation is included, the noncommutative effect appears in the two-body decay process. The discrepancy between the experimental branch ratio and the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…A detailed study on the photon-neutrino interaction and its related phenomenology can be found in [47,74]. One can derive the Feynman rule from the lepton action [73,[84][85][86] by using equation (2.10,2.11) and equation (2.1) as follows Photon-Fermion-Fermion interaction:…”
Section: Top Quark Pair Production In the Covariant θ-Exact Ncsmmentioning
confidence: 99%
“…A detailed study on the photon-neutrino interaction and its related phenomenology can be found in [47,74]. One can derive the Feynman rule from the lepton action [73,[84][85][86] by using equation (2.10,2.11) and equation (2.1) as follows Photon-Fermion-Fermion interaction:…”
Section: Top Quark Pair Production In the Covariant θ-Exact Ncsmmentioning
confidence: 99%
“…Furthermore, it is naturally formulated in a Lorentz covariant way. Hence, it was used in various quantum system, ranging form low energy atom physics [37] to the hight energy collision processes [50,50,51]. We will use the SW map to study the noncommutative corrections.…”
Section: Covariant Nonvommutative Ab Effectmentioning
confidence: 99%
“…For the coordinate noncommutativity, it has been shown that the SW map [1] from the noncommmutative space to the ordinary one preserves the gauge symmetry and has been proven to be very useful in investigating various problems on noncommutative space [38,[53][54][55][56][57][58][59][60]. Therefore, we will use the SW map to study the noncommutative corrections induced by the nontrivial algebra in (1).…”
Section: Noncommutative Hamiltonianmentioning
confidence: 99%